Peningkatan Kapasitas Produksi Gummy Candy Sehat Berbasis Buah Lokal melalui Pelatihan dan Transfer Teknologi - Citrariana, Shesanthi; Ayu, Regina Wahyudyah Sonata; Riani, Defilia; Desindria, Galang Rizdho; Yosaeunike, Vitatani; Febrianto, Yahya; Alfanaar, Rokiy; Rahman, Sudarman; Suprayogi, Thathit; Arsana, Mu afa; Fatiqin, Awalul (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
The problem of fruit waste due to oversupply in agritourism, which causes economic losses and environmental burdens, is the focus of this community service activity. The program aims to enhance partners' capacity through training and technology transfer in producing healthy gummy candy from local fruits. Implementation methods included observation, socialization, practical training, and evaluation involving 20 participants from Agrowisata Cipta Rasa Pak Slamet. The results showed significant improvement in three aspects: conceptual and material understanding (85-90%), procedural skills (95%), and partner enthusiasm and motivation (100%). The implementation of green economy principles was achieved through the conversion of fruit surplus into high-value products with extended shelf life. This program successfully established a strong production foundation while creating a sustainable green value chain. It is concluded that the participatory training approach effectively empowers partners and is ready to be replicated in other locations with similar problems. Program sustainability is ensured through partner commitment and an agreed-upon production monitoring plan.